DISPUTES AS AN EARLY MODERN PEDAGOGICAL FORM OF IMPLEMENTATION OF THE HUMANISTIC IDEA OF HOLISTIC PERSONAL EDUCATION - Басенко, Руслан (SWorldJournal, 2025)
The article is devoted to the analysis of disputes as an early modern pedagogical form of implementing the humanistic idea of ​​holistic education of the individual. It is stated that disputes made it possible to implement the idea of ​​holistic educatio